One Integrated Service Quality Doors at Meureudu State Court - Mimin Suriadi; Rozaili Rozaili; Zulfikar Zulfikar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
One door integrated service policy is a new idea in service to the community. Integrated steps in this service are system changes in the implementation of activities to facilitate the Meureudu district court in serving the community, this policy requires processes and innovations for service providers, one door integrated service guidance and direction full of today's technological challenges., the role in the system that is carried out cannot be separated from the challenges of circumstances that can cause deviations in an activity. The authors use a descriptive qualitative approach which is basically an attempt to reveal a problem or situation or event as it should be so as to provide an objective picture of the actual state of the object under study. Research results and discussion, In improving services to the needs of the community, the Meureudu district court has facilitated and guided its employees in providing services, a simple, fast and precise service process requires the ability and creativity of employees and for the implementation of these activities this greatly affects the leadership role that manages the wheels of activity in the court. The success of the Meureudu District Court by obtaining a B rating means that demands for excellent service to the community are the first priority. The obstacle faced by the Meureudu District Court is that they do not have their own building and they are still using the Pidie Jaya Regency government building which has been granted the right to use this greeting. fast and precise requires the ability and creativity of employees and for the implementation of this activity is very influential in the leadership role that manages the wheels of activity in the court.